Political Commitment of Hmong Americans: A Study of a Grassroots Feminist Movement Against Abusive International Marriages 2007-2022. - (:unkn) unknown (My University, 2023)
This thesis examines the Hmong American community-led movement against abusive international marriages (AIM) in Wisconsin as an instance of activism or resistance related to marriage-migration phenomena in the 21st century. Through an analysis of oral histories of Hmong American community activists, Hmong American community media, archival materials, born-digital sources, and other contemporary sources, this study incorporates experiences underexplored in U.S. historical scholarship. The findings unearth that the feminist movement against AIM emerged not solely as an active response to a trend of gender-based violence cases in the early 2000s but also as a resistance to the persisting stigmatization from the dominant American society and institutions. The gendered perspective, intersected with awareness of race and class issues, has been a central element in the movement as part of its strategy to foster a gender justice agenda. I argue that the Hmong American grassroots feminist movement against AIM is based on a political commitment to a liberation struggle against sexism, racism, and classism rather than being solely grounded on shared victimization. This political commitment has created an alternative form of belonging among Hmong American community advocates and organizers, which extends to the Hmong transnational community.
Keywords: Abusive International Marriages; Feminist Movement; Grassroots; Hmong American; Marriage Migration; Resistance